[Rezension von: Elliott, Mark W., 1965-, Providence : A Biblical, Historical, and Theological Account] - Wright, Terry J; Elliott, Mark W. 1965- (2021)
This is the third entry in Mark Elliott’s loose trilogy on the subject. Whereas The Heart of Biblical Theology: Providence Experienced (Ashgate, 2012) championed the concept of providence as a way to promote dialogue between biblical studies and systematic theology, and Providence Perceived: Divine Action from a Human Point of View (De Gruyter, 2015) (see JTS, ns 68 [2017], pp. 866-8) supplied a historical overview of the doctrine, Providence: A Biblical, Historical, and Theological Account is, as its subtitle suggests, a study of providence, as both concept and reality, in Scripture, history, and systematic theology. The result is an insightful but sometimes unfocused exploration of an important theme.
Keywords: Rezension